A possible role for sarcosine in the management of schizophrenia. (December 2019) - Curtis, David
Summary: Sarcosine, which is freely sold as a dietary supplement, has pharmacological activity to boost functioning of the glutamatergic N -methyl-d -aspartate receptor (NMDAR) and hence it is a biologically rational treatment for schizophrenia. The small number of studies carried out to date provide some evidence for its efficacy and psychiatrists could consider suggesting its use to their patients.